دور شبكات التواصل الاجتماعي في الحفاظ على التراث المحلي لدى فئة الطلبة الجامعيين - برطال يونس; د/ علال عبدالقادر (جامعة عمار ثليجي الاغواط, 2024)
الملخص : تهدف دراستنا الى معرفة "دور شبكات التواصل الاجتماعي في الحفاظ على التراث المحلي لدى فئة الطلبة الجامعيين" خاصة الفيسبوك الذي يعتبر وسيلة فعالة محليا حيث يمكن استخدامه في التوعية و الحفاظ على التراث الثقافي ، وتهدف دراستنا من خلال البحث ابراز دور هذا الموقع في الحفاظ على موروثنا الثقافي لدى عينة الطلبة الجامعيين حيث يستطيع الطلاب المشاركة و تنظيم مشاريع ترميم و صيانة المواقع التاريخية و المساهمة في الحفاظ على التراث و مدى تفاعلهم من خلال صفحة "الديوان الوطني للحظيرة الثقافية للأطلس الصحراوي" على الفايسبوك. تندرج هذه الدراسة ضمن الدراسات الوصفية التي اعتمدنا فيها على المنهج الوصفي كونه يهتم بدراسة الواقع و يساعد في الحصول على معلومات شاملة حول موضوع دراستنا ، تناولت الدراسة ثلاثة فصول نظرية الأول خصص للإطار المفاهيمي للتراث المادي و اللامادي أما الفصل الثاني فقد تناول فيه التراث المحلي في الجزائر واقعه و دور وسائل الاعلام ، أما الفصل الثالث حول شبكات التواصل الاجتماعي و الفيسبوك ، كما شملت الجانب الميداني حيث جرى فيه معالجة البيانات التي جمعناها حول مساهمة صفحة الديوان الوطني للحظيرة الثقافية للأطلس الصحراوي في الحفاظ على التراث لدي فئة الطلبة الجامعيين لنتوصل الى مجموعة من البيانات أهمها : ان الصفحة الرسمية للديوان على الفايسبوك تقوم بنشر معلومات حول التراث المحلي و حمايته من التخريب و السرقة كما يتفاعل طلبة جامعة عمار ثليجي مع المحتوى المنشور من خلال التعاليق و المشاركة وكذا الاستعداد لتبني فكرة المحافظة على هذا الموروث المحلي و ضمان بقائه . الكلمات المفتاحية : شبكات التواصل الاجتماعي ، التراث المحلي ، الطلبة الجامعيين. Summary: Our study is aimed at learning "The role of social media in preserving the local heritage of university students," especially Facebook, which is an effective local means of raising awareness and preserving cultural heritage. Through research, our study aims to highlight the role of this site in preserving our cultural heritage in the sample of university students where students can participate, organize projects for the restoration and maintenance of historical sites and contribute to the preservation of heritage and their interaction through the Facebook page of the National Office of the Desert Atlas Cultural Park. This study is part of the descriptive studies in which we have relied on the descriptive method of studying reality and helping to obtain comprehensive information on the subject of our study. The study covered three theoretical chapters: the conceptual framework for material and non-material heritage. Chapter II dealt with the local heritage in Algeria and the role of the media. Chapter III, on social media networks and Facebook, covered the field area where the data collected on the contribution of the page of the National Office for the Cultural Corner of the Sahrawi Atlas to the preservation of the heritage of university students, was processed in order to arrive at a set of data, the most important of which is as follows: The official Facebook page of the Office disseminates information about the local heritage and protects it from vandalism and theft. Students at the University of AmmarThlaji interact with the published content by means of comment and participation, as well as by preparing to adopt the idea of preserving this local heritage and ensuring its survival. Keywords: social networking, local heritage, universitystudents
دراسة على عينة من طلبة جامعة الاغواط من متتبعي صفحة الديوان الوطني الثقافي للاطلس الصحراوي الرسمية على الفيسبوك